The challenging increase of renewable energy use. The law as a tool for the evolution of Brazilian wind power promotion policies - Nusdeo, Ana Maria (2022)
Energy policy is an important aspect of climate mitigation policies and can be analyzed under a holistic approach of public policies understood as a coordination of ends and means related to governmental acts for maintaining or changing the status quo in a specific matter. In the case of power generation, that change of status quo regards the promotion of alternative sources. The purpose of this article is the analysis of the Brazilian energy policies implemented from 2002 to 2020, for the development and increase of the wind power source, that grew from 0%, in the beginning of the decade of 2000, before specific governmental policies, to 9,5% in 2020, analyzing their context, features and instruments.